The Impact of ICT on Profit Allocation within Multinational Groups: Arm's Length Pricing or Formula Apportionment? - Christoph Spengel; Anne Schäfer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
The use of information and communication technologies (ICT) within multinational groups leads to a rising number of intragroup cross-border transactions. At the same time, transactions and the organisational structures of affiliated groups become more and more specific and, thus, less comparable. The importance of human capital and of mobile factors of production, such as intangible assets, increases. The objective of this paper is to give an insight into the principal issues of profit allocation within multinational groups resulting from these economic changes. It is examined whether the traditional transaction methods based on the arm?s length principle can be upheld and to what extent the alternative method of formula apportionment is more suitable. The tax principles of inter-nation equity and feasibility are used to evaluate the different methods of profit allocation. We conclude that, in the light of the two demanded principles, formula apportionment is more appropriate than the arm?s length principle as regards the changed economic structures by use of ICT. As formula apportionment constitutes a suitable alternative especially in the European Union, the proposals made by the European Commission are considered to be a good starting point.
Keywords: H21; H25; 330; International Company Taxation; Profit Allocation; Transfer Pricing; Arm?s Length Principle; Formula Apportionment; Inter-Nation Equity; Multinationales Unternehmen; Gewinnverlagerung; Transferpreis; Internet; E-Business; Unternehmensbesteuerung; Doppelbesteuerung; Welt